Determination and application of interval swim critical velocity and critical rest time in the 50 m interval swim training - Wakayoshi, K.; Takano, C.; Ogita, F. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to determine critical velocity (VcriIS) and critical rest time (tcri) for interval training at four velocities higher than anaerobic threshold. Eleven well-trained College male swimmers performed four to six sets of 50m interval swim test (Tint) at each given velocity. The relations between total time (tT) and the total swim distance (Dint) of Tim were expressed in the general form, Dint=a+b*tT in all subjects. Vcri-IS could be determined by the relationship between Dint and tT. and tcri could be calculated from Vcri-IS and swimming time (ts) at each velocity. Moreover, combination swimming velocity, rest time and total swimming distance direction could be determined. It was thought that the combinations of velocity and rest period which imply interval training fatigue threshold (ITFT) could be defined from the results of VcriIS and tcri.